Determinants of Brand Equity in Ecuadorian Private Universities - Shegia, Bajaña-Villagomez Yanina; Ronalde, Camacho Villagómez Freddy (International Review of Management and Marketing, 2024)
This paper provides empirical evidence about the determinants of brand equity in higher education, using a sample of 211 students from Ecuadorian universities. Using findings of the literature we conduct a survey to construct some variables related to brand equity, named: brand awareness, brand image, perceived brand quality and brand loyalty. We test for the influence of these variables on brand equity trough a structural equation model. The results show that the measured variables are significant. Moreover, the model explains around 70% of the brand equity.